Evidence Value of Victims' Testimony In Sexual Violence Cases After The Approval of The TPKS Law (Law on Sexual Violence) - Nurfadia Faradila; Kayus Kayowuan Lewoleba (Dinasti Publisher, 2024)
This research aims to discuss the evidentiary value of victim-witness testimony in sexual violence cases after the ratification of the Sexual Violence Crime Law and to examine the obstacles that still exist after the ratification of the Sexual Violence Crime Law. Evidence in sexual violence cases already existed in the Criminal Procedure Code before the enactment of the Anti-Sexual Violence Law. 5 (five) types of valid and admissible evidence are emphasized in KUHAP Article 184, namely: letters, instructions, expert testimony, witness testimony, and confessions of suspects or defendants. Thus, to prove that the perpetrator is guilty and imprison the suspect becomes difficult due to these provisions and requirements. As a result, the suspect in the sexual violence case was acquitted. In addition, in current practice, proving the crime of sexual violence is still found several obstacles. The author in this research uses normative legal research methods with a statute approach and conceptual approach to examine the existing problems. The results of this study are expected to provide theoretical benefits, namely as a source of information for future researchers in the field of criminal law, especially related to the emphasis of the TPKS Law on the evidentiary value of victim witnesses. Then in terms of practical benefits, it is hoped that it can provide a new perspective and basic information for writers and readers to support further research on sexual violence in Indonesia, as well as assist law enforcement in an effort to protect victims of sexual violence in Indonesia.